Microtus (Microtus) ilaeus Thomas 1912 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Microtus (Microtus) ilaeus Thomas 1912 Microtus (Microtus) ilaeus Thomas 1912, Ann. Mag. Nat. Hist., ser. 8, 9: 348. Type Locality: Kazakhstan, Semirechyia, Djarkent, banks of Ussek River. Vernacular Names: Kazakhstan Vole. Synonyms: Microtus (Microtus) igromovi Meir, Golenischev, Radjably, and Sablina 1996; Microtus (Microtus) ileos Vinogradov 1930; Microtus (Microtus) innae Ognev 1950; Microtus (Microtus) kirgisorum (Ognev 1950). Distribution: W Uzbekistan just south of the Aral Sea, eastward through S Kazakhstan nearly to border south of Lake Balkhash (Meyer et al., 1996:128) and into NW Xinjiang Prov., NW China (Zhang et al., 1997). Conservation: IUCN – Lower Risk (lc) as M. kirgisorum . Discussion: Subgenus Microtus , arvalis species group (Meyer et al., 1996; Zagorodnyuk, 1990). Described as a subspecies of M. arvalis and later elevated to species (Meyer, 1983; Meyer et al., 1981), as now observed (Corbet, 1984; Gromov and Erbajeva, 1995; Musser and Carleton, 1993; Pavlinov and Rossolimo, 1987, 1995; Pavlinov et al., 1995 a ). Kovalskaya (1994) documented its distribution in E Kazakhstan, reported probable sympatry between M. kirgisorum and M. arvalis " obscurus " in the Ili River valley, and noted that the region circumscribed the type locality of Thomas’ ilaeus . Meyer et al. (1996) revised M. ilaeus , synonymizing kirgisorum and describing igromovi as a subspecies; Malygin and Luis (1996) associated innae with M. ilaeus . Chromosomal data (2n = 54, FN = 78) presented by Orlov et al. (1983), Kovalskaya (1994), and Meyer et al. (1996) in phylogenetic studies of the M. arvalis group. Histoenzymatic indices of specific skin glands also support the specific status of M. ilaeus (Sokolov and Dzhemukhadze, 1995, as kirgisorum ). The species closely resembles the southern M. transcaspicus in pelage coloration, large body size, and karyotype (2n = 52 for M. transcaspicus ) and is also closely allied to M. levis (Meyer et al., 1996). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Rodentia ...